PERBANDINGAN PENGARUH KECEPATAN ARUS AIR TERHADAP LAJU KOROSI DAN KEKERASAN PADA ALUMUNIUM DAN BAJA KARBON SEBAGAI PROTOTIPE PLAT BODY KAPAL - MS, Firdaus; Saud, Eddy; Pasayu, Deliansyah; Yosieguspa, Yosieguspa; Hidayat, Aldi; Febriyanto, Agung (TURBO [Tulisan Riset Berbasis Online], 2025)
This study aims to determine the comparison of the effect of air flow velocity on the corrosion rate and hardness of aluminum and carbon steel materials. This study is an experimental study using specimens, namely Aluminum 6061 and low carbon steel AISI 1018. The results showed that 1) the immersion current velocity for 2 days obtained the following results, for the speed with a distance of 12 cm from the dynamo, a speed of 0.073 m / s was obtained for aluminum. Something that is not much different is also obtained for the speed of low carbon steel where with a distance of 12 cm from the dynamo, a speed of 0.075 m / s was obtained. 2) The difference in weight between before and after immersion in the specimen shows that in aluminum the weight difference is smaller than the weight difference in low carbon steel. 3) The corrosion rate of low carbon steel is higher than aluminum. This shows that aluminum is more resistant to corrosion